Pragmatic options for dose optimization of ceftazidime/avibactam with aztreonam in complex patients. (30th December 2020) - Falcone, Marco; Menichetti, Francesco; Cattaneo, Dario; Tiseo, Giusy; Baldelli, Sara; Galfo, Valentina; Leonildi, Alessandro; Tagliaferri, Enrico; Di Paolo, Antonello; Pai, Manjunath P
Abstract: Background: Avibactam is a β-lactamase inhibitor that is combined with aztreonam against Enterobacterales co-expressing serine- and metallo-β-lactamases (MBL). Optimal dosing of aztreonam with avibactam is not well-defined in critically ill patients and contingent on ceftazidime/avibactam product labelling. Objectives: To identify a pragmatic dosing strategy for aztreonam with avibactam to maximize the probability of target attainment (PTA). Methods: We conducted a prospective observational pharmacokinetic study. Five blood samples were collected around the fourth dose of aztreonam or ceftazidime/avibactam and assayed for all three drugs. Population pharmacokinetic (PK) analysis coupled with Monte Carlo simulations were used to create a dosing nomogram for aztreonam and ceftazidime/avibactam based on drug-specific pharmacodynamic (PD) targets. Results: A total of 41 participants (59% male) median age of 75 years (IQR 63–79 years) were enrolled. They were critically ill (46%) with multiple comorbidities and complications including burns (20%). Population PK analysis identified higher volume of distribution and lower clearance (CL) compared with typical value expectations for aztreonam and ceftazidime/avibactam. Estimated glomerular filtration (eGFR) rate using the CKD-EPI equation predicted CL for all three drugs. The need for high doses of aztreonam and ceftazidime/avibactam above those in the existing product labels are not predicted by this analysis with the exception of ceftazidime/avibactam for patients with eGFR of 6–15 mL/min, in whom suboptimal PTA of ≤71% is predicted. Conclusions: Pragmatic and lower daily-dose options are predicted for aztreonam and ceftazidime/avibactam when the eGFR is <90 mL/min. These options should be tested prospectively.